Effects of organic fertilizer and plant spacing on early-medium maturity soybean - Henny Kuntyastuti; Sri Ayu Dwi Lestari; S Sutrisno (Journal of Degraded and Mining Lands Management, 2018)
Efforts to increase soybean productivity must be synergy with the improvement of soil fertility through fertilizer, especially organic fertilizer. Population density of a crop determines to a greater extent its performance in terms of soybean yield. Based on the two cultivation techniques mention above, that is expected to increase soybean productivity. The objective of this research was to obtain organic fertilizer and plant spacing that can support the development of early-medium maturity soybean (Lokal Jateng soybean lines/Sinabung-1036) to achieve 3 ton dry seed per hectare. The research was conducted at Alfisol soil Muneng Station Research, Probolinggo and at Entisol soil Genteng Station Research, Banyuwangi on dry season (DS) 2012. The experiment used split plot design with three replications. As the main plot was plant spacing, namely: 1) 40 cm x 10 cm, 2 plants/hole, 2) 40 cm x 15 cm, 2 plants/hole, 3) 40 cm x 20 cm, 1 plant/hole, and 4) 40 cm x 20 cm, 2 plants/hole. As the sub plot were four doses and types of organic fertilizer, namely: 1) without organic fertilizer, 2) 2.5 t manure/ha, 3) 5 t manure/ha, and 4) 2 t Santap NM-2/ha. The result showed that the potential yield of 3 t/ha for large, early-medium maturity soybean could not be achieved at Alfisol soil Probolinggo and at Entisol soil Banyuwangi by planting soybean of Lokal Jateng soybean lines/Sinabung-1036 with plant spacing 40 cm x 10-20 cm, 1-2 plants/hole and application of 2.5-5 t manure/ha or 2 t Santap NM-2/ha